A Study on Central Moments of the Histograms from Scanning Electron Microscope Charging Images - Tan, Y. Y.; Sim, K. S.; Tso, C. P. (JOHN WILEY & SONS INC, 2007)
This paper presents a study on using the statistical parameter, central moment, to describe the properties of the histograms of scanning electron microscope (SEM) images. Various charging effects of SEM images and the corresponding histogram profiles are analyzed. The central moment distributions are used to describe the overview of the histograms of an image. The results show that central moments can be used to quantify and characterize the charging images. In particular, the second moment (variance) and third moment (skewness) can be used to distinguish the differences between charging and noncharging images.